Dystopian utopia between mountain and the sea? Second-home production along the Coastal Cordillera of Central Chile 1992-2012 - Hidalgo, Rodrigo; Rivas, Luis Daniel Santana; Haller, Andreas; Borsdorf, Axel (DIE ERDE – Journal of the Geographical Society of Berlin, 2017)
In recent decades the expansion of the metropolitan areas in Central Chile has produced numerous forms, structures and functions. The amenities of the environment and local food and culture have been used to promote a utopia for future residents, which include many people who have purchased a second home. However in many cases the migrants have suffered frustrations. They found dystopia instead of the promised utopia. By intensifying the metropolization of Central Chile, the real estate sector has produced a space not unlike the spatial conditions the migrants hoped to escape. Pristine environments were transformed into polluted areas, suffering from rapid urbanization, noise, rubbish and an overload of visitors in formerly untouched areas. In this paper we analyse the socio-economic impact and the perception of second-home development. Many of the new apartments, flats and houses are used as second homes, introducing and enhancing new forms of multilocality. The infrastructure is designed for full occupation, yet during many periods of the year it is not used, and those who live there all year round seem lost in large areas devoid of life.